Meningkatkan Hasil Belajar dan Sikap Gotong Royong Menggunakan Model PBL Berbantuan Media Game Puzzle Pada Siswa Fase A Kelas II SDN 034 Tarakan - Erni Sulistiyawati (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
The final of this research is to improve the result of study and attitude of “gotong royong” (mutual collaboration) using the model of problem based learning with the use of model of media game puzzle for the students of second grade of 034 Elementary School in Tarakan. The method of this research is the research in the classroom action. The technic of data analysis is collecting the data, reducing the data, presenting the data and making the conclusion, through the using the method of problem based on learning with the game puzzle model. This research is a respond to the lack of the activeness of the student during the lesson in classroom which will be causing the low of the study result and the attide of “gotong royong” / mutual collaboration which is becoming the one of the profile/ characteristic of “Pancasila” student. By using this method, the research shows the significat result of the study result of student. The increase was quite significant from the results of the first cycle post-test of 63.63 in cycle II to 86.36, namely 22.73% with the advanced category reaching 63.63% in accordance with the target, even exceeding the desired target (50% advanced). Beside of that, this method shows that there is a significant result of “gotong royong”/ “mutual collaboration” attitude among the student: 87,5%. The result of this reaserch is focusing on the effectivity in increasing the quality of classroom lesson. By involving the student actively and pushing the “gotong royong”/ mutual collaboration attitude , the collaboration and creativity during the lesson is not only becoming more interesting but also creating the important social values for the student.